An Extremely Deep Wide-Field Near-Infrared Survey: Bright Galaxy Counts and Local Large Scale Structure - Keenan, R C; Trouille, L; Barger, A J; Cowie, L L; W -H Wang (arXiv.org, 2009)
We present a deep, wide-field near-infrared (NIR) survey over five widely separated fields at high Galactic latitude covering a total of ~ 3 deg^2 in J, H, and Ks. The deepest areas of the data (~ 0.25 deg^2) extend to a 5 sigma limiting magnitude of JHKs > 24 in the AB magnitude system. Although depth and area vary from field to field, the overall depth and large area of this dataset make it one of the deepest wide-field NIR imaging surveys to date. This paper discusses the observations, data reduction, and bright galaxy counts in these fields. We compare the slope of the bright galaxy counts with the Two Micron All Sky Survey (2MASS) and other counts from the literature and explore the relationship between slope and supergalactic latitude. The slope near the supergalactic equator is sub- Euclidean on average pointing to the possibility of a decreasing average space density of galaxies by ~ 10-15% over scales of ~ 250-350 Mpc. On the contrary, the slope at high supergalactic latitudes is strongly super-Euclidean on average suggesting an increase in the space density of galaxies as one moves from the voids just above and below the supergalactic plane out to distances of ~ 250-350 Mpc. These results suggest that local large scale structure could be responsible for large discrepancies in the measured slope between different studies in the past. In addition, the local universe away from the supergalactic plane appears to be underdense by ~ 25-100% relative to the space densities of a few hundred megaparsecs distant. Subject headings: cosmology: observations and large scale structure of universe-galaxies: fundamental parameters (counts)-infrared: galaxies